Dance Theory as a Practice of Critique - Klein, Gabriele (Revista Brasileira de Estudos da Presença, 2021)
Using dance as an example, the text discusses the questions of what aesthetic criticism means and how it manifests itself. Drawing on philosophical and social science positions on critique (Foucault, Butler, Bourdieu), he develops a practical-theoretical view of the practice of critique in contemporary dance.